Robust and Feasible Buffer-Aided UAV Relay for Outage Probability Minimization - Salah Boubkar Salah Abdou; Chee Yen Leow; SeungHwan Won; Wee Kiat New; Abdullah M. Almasoud (Alexandria Engineering Journal)
Unmanned Aerial Vehicle (UAV) relay system is leading to considerable interests in 6G networks. However, high Outage Probability (OP) might still occur when non-buffering UAV transmits data directly. To address this critical issue, we explore the integration of a buffer-aided UAV relay and develop an Efficient Probability Based UAV (EP-UAV) scheme to reduce the OP efficiently while maintaining appropriate latency. Specifically, we analyze the proposed scheme under various buffer scenarios. Additionally, to further minimize the OP, we optimize the UAV’s 3D positions by keeping 1D-altitude-fixed and 2D-horizontal-coordinates-optimized, and then 1D-altitude-optimized while 2D-horizontal-coordinates-fixed. Simulation results manifest that the proposed scheme enables to minimize the OP and optimize its positions jointly. With the aid of the thorough analysis, our outcomes corroborate its feasibility for practical engineers.